Brazil : Higher Education Sector Study, Volume 1 - World Bank (Washington, DC, 2013)
Brazil has put significant resources into developing its higher education system over the past three decades. As a result, a system has evolved in which some institutions have achieved recognizable excellence in teaching and research, while, more generally, the majority of institutions have struggled to provide relevant, quality education at reasonable cost. As a whole, the system has a number of large challenges to overcome. Brazil has a low enrolment rate in higher education. Rigidities in funding and regulation create strong disincentives for cost-efficiency or quality. The quality of instruction and the relevance of the curriculum are below desirable standards. The Government of Brazil has a three-pronged strategy for improving higher education: a) to change the legal framework for the sector; b) to change to a performance-based funding system that supports (Ministerio da Educacao e do Esporto's (MEC) policy goals of improved access, quality, and efficiency; and c) to improve capacity for evaluating quality of instruction and performance of institutions. The challenge is to focus attention on those changes that will promote the greatest progress in equitable access, quality, relevance, and efficiency. In the last section, the report recommends ways to improve access, quality, and efficiency.